MathAlgebra
posted by Mike .
[SQRT(x + 3)]  [SQRT(x  2)] =1
Can someone help me solve this equation.

sqrt(x+3) = sqrt(x2) + 1
Square both sides.
x+3 = x2 + 2sqrt(x2) +1
2 = sqrt(x2)
4 = x2
x = 6
Respond to this Question
Similar Questions

Inequality
When I solve the inquality 2x^2  6 < 0, I get x < + or  sqrt(3) So how do I write the solution? 
math,algebra,help
Directions are simplify by combining like terms. x radiacal 18 3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces … 
math,help,algebra I
I need help can someone help me get unstuck and let me know if i am correct.thank you. solve by completing the square. 4x^2+2x3=0 this is what i am doing: i used the quadratic equation. so where i am is in this step: x = (2 (+) … 
Math Help please!!
Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine … 
Math/Calculus
Solve the initialvalue problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else? 
algebra
can someone tell me if i did the problem correct (solve by completing the square) 4x^2+2x3=0 x^2+(1/2)=3/4 x^2+(1/2)+(1/4)^2=3/4+(1/4)^2 (x+1/4)^2=13/16 x+1/4=+sqrt 13/16 x+1/4=+sqrt 13/4 x=1/4+sqrt 13/4 x=1+sqrt 13/4 
Algebra 2
Operations with Complex Numbers Simplify. 1. sqrt(144) 2. sqrt(64x^4) 3. sqrt(13)*sqrt(26) 4. (2i)(6i)(4i) 5. i13 6. i38 7. (5 – 2i) + (4 + 4i) 8. (3 – 4i) – (1 – 4i) 9. (3 + 4i)(3 – 4i) 10. (6 – 2i)(1 + i) 11. (4i)/(3+i) … 
Algebra
I have a question if someone could help, please explain it. Given b = 1 and h = 1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x1) b.y = sqrt (x+1) c.y =  sqrt (x1) d.y = sqrt(x1) … 
Surds
Solve in the exact form. (sqrt of 4x+1)+(sqrt of x+1)=2 Someone showed me to do this next: Square both sides..so.. 4x+1+2((sqrt of 4x+1)•(sqrt of x+1))=4 I do not understand where the 2 come from ..and why do we need to multiply … 
Algebra
Evaluate sqrt7x (sqrt x7 sqrt7) Show your work. sqrt(7)*sqrt(x)sqrt(7)*7*sqrt(7) sqrt(7*x)7*sqrt(7*7) sqrt(7x)7*sqrt(7^2) x*sqrt 7x49*x ^^^ would this be my final answer?